2000
DOI: 10.4049/jimmunol.165.8.4676
|View full text |Cite
|
Sign up to set email alerts
|

Human Monoclonal Antibodies Isolated from Type I Diabetes Patients Define Multiple Epitopes in the Protein Tyrosine Phosphatase-Like IA-2 Antigen

Abstract: Protein tyrosine phosphatase-like IA-2 autoantigen is one of the major targets of humoral autoimmunity in patients with insulin-dependant diabetes mellitus (IDDM). In an effort to define the epitopes recognized by autoantibodies against IA-2, we generated five human mAbs (hAbs) from peripheral B lymphocytes isolated from patients most of whom had been recently diagnosed for IDDM. Determination and fine mapping of the critical regions for autoantibody binding was performed by RIA using mutant and chimeric const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…IA-2Ab epitopes have been mapped using different approaches including the closely related IA-2␤ (70 -73), fusion proteins of IA-2 and IA-2␤ (74,75), and human monoclonal antibodies specific to IA-2 (76,77). IA-2 appears to be the primary autoantigen in type 1 diabetes, whereas antibodies to IA-2␤ are considered to be the result of subsequent epitope spreading (8,70,75,78).…”
Section: Daa Epitopesmentioning
confidence: 99%
See 2 more Smart Citations
“…IA-2Ab epitopes have been mapped using different approaches including the closely related IA-2␤ (70 -73), fusion proteins of IA-2 and IA-2␤ (74,75), and human monoclonal antibodies specific to IA-2 (76,77). IA-2 appears to be the primary autoantigen in type 1 diabetes, whereas antibodies to IA-2␤ are considered to be the result of subsequent epitope spreading (8,70,75,78).…”
Section: Daa Epitopesmentioning
confidence: 99%
“…High susceptibility HLA genotypes were associated with the presence of multiple epitopes to both IA-2 and IA-2␤, but not with IA-2Ab specific to the juxtamembrane region (78,80). In an effort to better characterize the conformational epitopes, competition assays with human monoclonal antibodies were developed (76). A major conformational epitope located at the COOH-terminal region of the protein tyrosine phosphatase domain was identified using this approach (76,77).…”
Section: Daa Epitopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified rFab KSAb1 or anti-TSHR mAbs were used as a positive control and rFab 96/3, specific for a pancreatic islet cell Ag IA-2, served as a negative control (33) for the bacterial produced Abs. Radioligand binding inhibition assay.…”
Section: Evaluation Of Reactivity Of Rfab Germline To Tshrmentioning
confidence: 99%
“…The finding that IA-2 (256 -760) construct reacts with more LADA patients than IA-2 FL (1-979) , even if the former is a portion of the latter, might be due to a different conformation of the 256 -760 amino acidic residues of the two constructs or to steric hindrances, ultimately leading to variable autoantibody binding affinities. Several studies demonstrated that IA-2As in type 1 diabetic patients are directed against multiple epitopes of the intracellular cytoplasmic portion of the protein (amino acids 601-979), located in the juxtamembrane region (JM, amino acids 605-682), and in the protein (PTP)-like COOH-terminal domain (amino acids 630 -979) (31)(32)(33)(34)(35)(36). To date, an immune response against the extracellular domain of the IA-2 protein has not been demonstrated in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%